Study on Ocular Surface Changes in Patients with Unilateral Pterygium Compared to their Normal Eye - Damarla, Nirupama; Bommisetti, Hymavathi; Chevuturi, Madhavi; Tadisina, Sanjay Reddy; Reddy, Satyanarayana; P., Likitha (Journal of Ophthalmology and Research, 2025)
Background: The purpose of our study was to estimate the variations between TBUT (Tear film breakup time) Schirmers test (ST)value and MGD(Meibomian gland dysfunction) between a normal eye and an eye with pterygium. Methods: 50 patients with unilateral pterygium were enrolled in our study. TBUT, ST measurements, MGD and conjunctival congestion were evaluated. The results were compared between eyes with pterygium (Cases)and normal eyes of the same patient (controls). Pterygium was graded based on the length of limbal invasion into 3 grades. We have also evaluated the relationship between grades of pterygium and TBUT and Schirmer I test . Results: The mean TBUT in cases(eyes with pterygium) was 5.16±1.89 seconds and the mean TBUT in controls(eyes without pterygium) was 7.00±1.47 seconds . The mean wetting length of Schirmer’s strip was 10.96±3.51mm in cases and 13.90±4.5 mm in controls. Schirmer’s test was statistically significant between the eyes with pterygium and eyes without pterygium with P < 0.0001. In patients with pterygium 36% had MGD (Meibomian gland dysfunction) of varying severity whereas 26.5% of eyes without pterygium had MGD. There was no association of MGD between eyes with pterygium and the eyes without pterygium. Conclusion: Our study has shown that TBUT and Schirmers test values have an association with pterygium.